Peningkatan Daya Saing Usaha Mikro melalui Program Pelatihan Sustaining Competitive and Responsible Enterprises - Lilian Danil*; Triyana Iskandarsyah; Nina Septina; Irsanti Hasyim; Teresia Debby (Universitas Lancang Kuning, 2023)
Micro, small, and medium-sized firms (MSMEs) are required to be highly competitive so that they may thrive in unpredictable markets and contribute to economic growth despite several challenges such as financing, market access, innovation, and productivity. Through the Sustaining Competitive and Responsible Enterprises (SCORE) program at Parahyangan Catholic University, Batch 6, the writing team provided training (workshops) and mentoring (coaching) to MSMEs in Bandung Regency. The major goal of the SCORE program is to help SMEs in Bandung Regency enhance their competitiveness so that they may use their own resources to achieve productivity and expand their competitive edge. The workshop program is implemented with topics such as teamwork and communication, increasing business productivity, financial records, determining the cost of goods sold (HPP), the use of promotional media, and increasing marketing understanding, while personal assistance is provided through visits to MSME production sites at least three times during the program. At the end of the program, there was a rise in MSMEs' development, indicating that 100% of MSMEs had participated in the provision and execution of information boards, HPP calculations, product innovation, and optimization of social media as a promotional medium. This success can help SMEs grow their capabilities, particularly in tackling some of the issues they confront, such as marketing, productivity, accounting, and budgetary restraints. With the settlement of these issues, the next step in strengthening the competitiveness of SMEs, aided by SCORE UNPAR in Bandung Regency, may be taken.